2020
DOI: 10.1016/j.heliyon.2020.e04917
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 nullified khat-induced hepatotoxicity, nephrotoxicity and inflammation in a mouse model

Abstract: The consumption of khat (Catha Edulis, Forsk) is on the rise despite the much publicized associated deleterious health effects. How chemicals present in khat, affect various physiological and biochemical processes requires further scrutiny. A clear understanding of these processes will provide an avenue for countering khat-driven negative effects using appropriate pharmacological and/or nutritional interventions.Aim of the study: The current study investigated the effect of khat on vital physiological and bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…This is in accordance with other data that showed the nephron‐protective effect of Co‐Q10 as respiratory substrate, antioxidant, and anti‐inflammatory agent. Co‐Q10 was shown previously to improve cisplatin and khat‐driven kidney oxidative stress and inflammation in rats (Kennedy et al, 2020; Khalifa et al, 2020) In addition, Co‐Q10 was reported to improve mitochondrial dysfunction of tacrolimus‐induced kidney failure (Yu et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…This is in accordance with other data that showed the nephron‐protective effect of Co‐Q10 as respiratory substrate, antioxidant, and anti‐inflammatory agent. Co‐Q10 was shown previously to improve cisplatin and khat‐driven kidney oxidative stress and inflammation in rats (Kennedy et al, 2020; Khalifa et al, 2020) In addition, Co‐Q10 was reported to improve mitochondrial dysfunction of tacrolimus‐induced kidney failure (Yu et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, depletion of hemoglobin in the current study, possibly confirmed a decrease in RBCs which is consistent with the elevation of the total bilirubin level in the plasma; perhaps due to GBH-induced hemolysis. Reduction of GSH and increased lipid peroxidation of RBCs has been reported to result in cellular lysis ( Kennedy et al, 2020 , Jasper et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since CoQ10 has been shown to have potent antioxidant and anti-inflammatory effects, Kennedy et al. [ 52 ] investigated the exact roles of CoQ10 in khat-induced AKI and found that CoQ10 (200 mg/kg, orally) significantly decreased creatinine levels and reduced tubular necrosis and tubular epithelium injury. The protective effect derived from CoQ10 might be associated with the reduction of oxidative stress and inflammation…”
Section: Protective Properties Of Coq10 In Aki Reported In Experiment...mentioning
confidence: 99%
“… 30 mg/kg, orally NA CoQ10 could not alleviate diclofenac-induced renal injury, but worsened impaired renal function Kennedy et al. 2020 [ 52 ] Mice Khat-induced nephrotoxicity (1500 mg/kg, gastric gavage) 200 mg/kg, orally Normalization of GSH and TNF-α expression CoQ10 decreased creatinine levels and reduced tubular necrosis and tubular epithelium injury Megrin et al. 2020 [ 53 ] Rats Lead-acetate-induced renal injury 10 mg/kg, intraperitoneally Upregulation Nrf2/HO-1 pathway CoQ10 reduced the deleterious cellular side effects of lead acetate exposure owing to its antioxidant, anti-inflammatory, and anti-apoptotic effects Abdeen et al.…”
Section: Introductionmentioning
confidence: 99%